De la géographie des professeurs à la géographie de l’action : une place nouvelle dans l’enseignement secondaire - Bernadette Mérenne-Schoumaker (Belgeo)
Within 50 years, school geography changed drastically, especially in the secondary schools of French-speaking Belgium. This evolution, made of four major phases, is related with the changes of both, societies and values. Although school geography is not any more a « reduction » of academic geography, its evolution is also related with the changes that took place within universities.On the basis of a SWOT analysis, forces and weaknesses of this secondary school geography are underlined and some action proposals are suggested.